Relationship of Self Concept, Problem Solving and Self Adjustment in Youth - Noviandari, Harwanti; Mursidi, Agus (International Journal for Educational and Vocational Studies, 2019)
This study aims to find a relationship between self-concept and problem solving with adapting to adolescents. The research subjects were 138 teenagers in class VII of SMP Negeri 3 Banyuwangi. Data collection is done by using the scale of self-concept, problem solving scale and scale of adjustment in adolescents that are compiled by researchers themselves. These three scales use a Likert model consisting of 5 alternative answers. Data were analyzed using regression analysis. The results of the study show (1) There is a significant relationship between self-concept and problem solving with adjustment variables in adolescents; (2) There is a very significant positive relationship between self-concept and adjustment in adolescents; and (3) There is a very significant positive relationship between problem solving and adjustment in adolescents. Effective contributions from self-concept variables and problem solving together have an effect of 40.5% on adapting to adolescents, so there are 59.5% of other variables that influence adolescents' adaptation in addition to the two X variables studied.